Techniques for Taking Pictures of Learning Videos in Learning Media - Amir, Day Ramadhani (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This research aims to find out an explanation of video shooting techniques in learning media in the form of learning videos. This type of research uses a qualitative descriptive research approach. This research uses a literature study method from various journal literature and books which can strengthen material about video shooting techniques. The data collection technique in this research uses library research and internet searching to find supporting data or information. The results of the research show that the learning video shooting techniques in the form of Extreme Long Shot, Very Long Shot, Long Shot, Knee Shot, Medium Shot, Medium Close Up, Close Up, Big Close Up, Extreme Close Up and Low Angle, Eye Level, High Angle are correct and in accordance with applicable rules